The change characteristics of dissolved copper in water of the Hun River, China. Issue 1 (January 2021) - Zhang, Kan; Li, Haifu; Lan, Tianhui; Su, Fangli
Abstract: The concentrations of dissolved copper in water of the Hun River were investigated to research the change characteristics of dissolved copper. We established the dynamic concentration function about time and spatial coordinate and convection diffusion equation of dissolved copper to obtain the distribution and accumulation characteristics of dissolved copper in the Hun River. In addition, we analyzed the advantages and disadvantages of two types of concentration functions of dissolved copper and used their own advantages to research the distribution and accumulation characteristics of dissolved copper in the Hun River. The results revealed the sources of copper pollution in water of the Hun River and provided theory basis to control copper pollution along the Hun River basin.